Identifying opportunities for enhanced hamstring health through improved running mechanics and proper loading progressions - Hansen, D. M. (New Studies in Athletics, 2014)
One of the biggest fears for athletes or other sportsmen and women who engage in high-speed running is the hamstring strain and its effect on performance. One study reports that hamstring injuries make up 26% of all injuries in athletics, with the majority being in the sprint events. A comprehensive approach for the prevention and treatment of hamstring strains must involve an assessment of the causes of the injury. Until we know exactly why hamstring strains occur, it is very difficult to minimise their incidence. Written by an experienced speed, strength and conditioning coach who has worked with sprinters and players from several other sports, this article provides coaches with basic anatomical and functional knowledge of the hamstrings os it relates to sprinting, identifies the risk factors of which they need to be aware and gives clues as to what to observe in order to assess the likelihood of a hamstring injury. The author then gives five recommendations for minimising the chance on injury before concluding that there is no one-size-fits-all programme and the coaches need to create individualised prevention programmes for their athletes.